Implementasi Mesin Sangrai pada UKM Penghasil Kacang Kulit Sangrai di Kenagarian Mungo Kabupaten Limapuluh Kota - Nelvia Iryani; Faisal Ali Ahmad; Nur Ari Sufiawan; Alfikri Alfikri (Warta Pengabdian Andalas, 2020)
The partner in this Community Partnership Program (PKM) Helping Businesses to Develop program is the Empat Saudara, owned by Rianto Saputra in Jorong Indobaleh Timur Kenagarian Mungo, Limapuluh Kota Regency. Currently, partners have significant problems in the aspects of production and marketing. The roasted peanut production process is traditionally done using an iron pan and sand by turning the beans using a wooden spoon. The quality and production capacity is limited. The purpose of this community engagement was to improve the product quality and production capacity of partners every day. The method provided education related to entrepreneurship training, such as production management, resource management, marketing and discussions about the problems partners face in running their business. It was followed by assisting production technology innovation using a 50 kg roaster machine at partner locations. This activity hopes to achieve a common goal, namely improving product quality and production volume, and ultimately raising the finances of the roasted peanut SMEs community.